2021
DOI: 10.1002/hipo.23312
|View full text |Cite
|
Sign up to set email alerts
|

Sodium salicylate enhances neural excitation via reducing GABAergic transmission in the dentate gyrus area of rat hippocampus in vivo

Abstract: Sodium salicylate, one of the non‐steroidal anti‐inflammatory drugs, is widely prescribed in the clinic, but a high dose of usage can cause hyperactivity in the central nervous system, including the hippocampus. At present, the neural mechanism underlying the induced hyperactivity is not fully understood, in particular, in the hippocampus under an in vivo condition. In this study, we found that systemic administration of sodium salicylate increased the field excitatory postsynaptic potential slope and the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In order to explore the possible mechanism of fullerenol in protecting hippocampus from being injured by lead, in vivo extracellular field potential recording has been used in our study. Unlike in vitro intracellular electrophysiology recording, it may be more truly and completely reflect the efficacy of drugs, through some important indicators such as I/O function, PPF ratio and LTP [ 27 , 28 ]. Two major pathways into and out of the hippocampus (the PP-DG pathway and the SCh-CA1 pathway), coordinately maintain synaptic transmission in hippocampus and are suitable to verify the possible effect of synaptic plasticity in the process of fullerenol against lead-induced injury [ 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the possible mechanism of fullerenol in protecting hippocampus from being injured by lead, in vivo extracellular field potential recording has been used in our study. Unlike in vitro intracellular electrophysiology recording, it may be more truly and completely reflect the efficacy of drugs, through some important indicators such as I/O function, PPF ratio and LTP [ 27 , 28 ]. Two major pathways into and out of the hippocampus (the PP-DG pathway and the SCh-CA1 pathway), coordinately maintain synaptic transmission in hippocampus and are suitable to verify the possible effect of synaptic plasticity in the process of fullerenol against lead-induced injury [ 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…SS can cause neuronal excitotoxicity by inhibiting GABA A R function [ 10 , 23 ], but the molecular mechanism is not fully understood. Research showed that the cochlear response of the D1 knockout mice was enhanced, and the auditory brainstem response (ABR) threshold of all frequencies was increased by 5–20 dB [ 12 ], indicating that D1Rs play an important role in auditory function.…”
Section: Discussionmentioning
confidence: 99%